The Portrayal of Agoraphobia in Under Rose- Tainted Skies’ Main Character - Alda Putri Zahara; Ely Nurmaily S.S,M.Hum (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This research discusses a novel written by Louise Gornal entitled Under Rose-Tainted Skies. this novel is tells the story about Norah as the main character who suffers the case of agoraphobia in her life after she got an accident of indland tsunami, the impact of that incident make herself has a million thought and make herself afraid of many things reflected to the social life and society. in this novel the author tells the reader about the condition of Norah in the story directly through her daily life and shown by the struggle of her during deal with her psychological condition as the agoraphobia sufferer in the novel. in this study, the researcher uses the descriptive qualitative methodology to describe the phenomena of agoraphobia that suffered by the main character in the novel Under Rose-Tainted Skies written by Louise Gornal. the data of this research is the quotation that taken by the novel that written by Louise Gornal as the primary data source. this thesis applies the theory of psychological of literature to support the theory of agoraphobia that will be used to analyze the case that faced by the main character Norah in the novel Under Rose-Tainted Skies. in this study, there are four symptoms that exist as the proof of the main character suffering agoraphobia in the novel, such as: Marked fear or anxiety about two (or more) of the following situations, avoid certain situations and require the presence of a companion, the fear or anxiety is out of proportion, significant distress or impairment in social life.this paper shows that the main character Norah in the novel Under Rose-Tainted Skies written by Louise Gornal as the person who suffered Agoraphobia from the daily activities of the main character in the novel. the main character shows the behaviors that reflected to the symptoms of agoraphobia in the nove, and the author give the portrayal of the main character suffering this mental issue with her surroundings.